Enhancement of the functional properties of vegetable sponge beverage fermented with Lactobacillus plantarum isolated from Korean dongchimi. (1st August 2022) - Jeong, Chang Hee; Hwang, Hyelyeon; Lee, Ho Jae; Kim, Tae-Woon; Ko, Hye In; Jang, Da Eun; Sim, Jae-Geun; Park, Byung-Geon; Hong, Sung Wook
Abstract: This study aimed to enhance the functional activities of vegetable sponge beverage (VSB) through fermentation. A total of 300 species of lactic acid bacteria, isolated from 6 types of kimchi, were screened to obtain the one suitable for fermenting a VSB with high sugar content. The selected strain was identified as Lactobacillus plantarum WiKim0067 by 16S rRNA gene sequence analysis. The treatment groups were set as LCC (fermentation broth) and LFP (freeze-dried powder), depending on the strain inoculation method. Both treatment groups showed a higher number of Lactobacillus than the control (VSB) group during storage. In particular, LFP showed similar level of sensory attributes as VSB. Subsequently, probiotic properties of LFP were investigated. After 1 and 2 months of bacterial inoculation, contents of lactic acid and acetic acid were increased in LFP. Moreover, LFP exhibited significantly higher superoxide dismutase (85.67%) and radical scavenging (71.14%) activities than VSB (71.88 and 55.68%, respectively). In addition, LFP treatment decreased the production of lipopolysaccharide-induced nitric oxide, interleukin (IL)-6, and IL-1β more than VSB treatment in RAW264.7 cells. Taken together, our results suggested that fermentation with L. plantarum WiKim0067 could enhance functional activities of VSB without affecting the sensory properties negatively. Highlights: Enhancement of functional activities of vegetable sponge beverage (VSB) was studied. Lactobacillus plantarum WiKim0067 could ferment VSB with high sugar content. Freeze-dried powdered strain (LFP) enhanced enzyme activities than in control VSB. Lactic acid and acetic acid contents increased in LFP group. Fermentation enhanced functional activities, but did not affect sensory properties.